2021
DOI: 10.3390/biomedicines9060683
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Infection with High Risk Human Papilloma Viruses among HIV-Positive Women with Clinical Manifestations of Tuberculosis in a Middle-Income Country

Abstract: Women living with HIV-1 are at high risk of infection with human papillomavirus of high carcinogenic risk (HR HPVs). M. tuberculosis (TB) promotes HPV infection and increases the risk to develop HPV-associated cancer. Our knowledge of persisting HR HPVs genotypes, and of the factors promoting HR HPV infection in people living with HIV-1 with clinical TB manifestations is sparse. Here, we analyzed 58 women living with HIV-1 with clinical TB manifestations (WLWH with TB) followed up in specialized centers in Rus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…The session was concluded with another study on HPV therapeutic vaccine research given by Dr. Juris Jansons (Latvian Biomedical Research and Study Center, and Riga Stradins University, Riga, Latvia), who presented results of DNA immunization of mice with HPV 16 E6 and E7. The study by Jansons et al evaluated the immunogenicity of the consensus HPV16 E6 and E7 designed after the analysis of HPV16 E6/7 sequences isolated from 35 HIV, TB or HIV/TB coinfected patients, which were found to be identical to the sequence of the reference HPV16 strain except for single amino acid substitutions [ 47 ]. Namely, 50% of the analyzed sequences of E6 contained substitutions of either R17G or L90V, or both.…”
Section: Session 4: Cancer Vaccinesmentioning
confidence: 99%
“…The session was concluded with another study on HPV therapeutic vaccine research given by Dr. Juris Jansons (Latvian Biomedical Research and Study Center, and Riga Stradins University, Riga, Latvia), who presented results of DNA immunization of mice with HPV 16 E6 and E7. The study by Jansons et al evaluated the immunogenicity of the consensus HPV16 E6 and E7 designed after the analysis of HPV16 E6/7 sequences isolated from 35 HIV, TB or HIV/TB coinfected patients, which were found to be identical to the sequence of the reference HPV16 strain except for single amino acid substitutions [ 47 ]. Namely, 50% of the analyzed sequences of E6 contained substitutions of either R17G or L90V, or both.…”
Section: Session 4: Cancer Vaccinesmentioning
confidence: 99%
“…Two (16 and 18) of the 150 HPV serotypes are oncogenic types. In the anogenital region, HPV infections can cause diseases such as condylomas or squamous cell carcinomas [1,2]. Often, our immunity can spontaneously clear off most HPV infections without treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies in Gurage Ethiopia also showed that the prevalence of HPV infection was 17.3%; which is a relatively high prevalence [8]. 2 Contrary to other malignancies of the reproductive system, cervical cancer can be avoided by early detection of a precancerous lesion through screening and treatment of lesions. Any one of the three techniques can be used to identify such lesions; human papillomavirus (HPV) Deoxyribose Nucleic Acid (DNA) test, pap smear, and visual inspection with acetic acid [9,10].…”
Section: Introductionmentioning
confidence: 99%